2001
DOI: 10.1046/j.1365-2265.2001.01320.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary risk in growth hormone deficient hypopituitary adults: increased predicted risk is due largely to lipid profile abnormalities

Abstract: Changes in lipid levels help to explain the results from risk factor modelling which show increased coronary risk in growth hormone deficient hypopituitary patients, particularly females. The abnormal lipid profile is characterized in both genders by an increase in the total to HDL ratio [corrected], an important parameter in the Framingham equation. The lipid abnormalities conferring increased risk is related to growth hormone deficiency either directly (LDL) or indirectly through increased central obesity (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
3
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 41 publications
6
64
3
2
Order By: Relevance
“…Several studies have shown that adult patients with untreated GHD present with a series of cardiovascular risk factors including increased blood pressure, increased BMI, abnormal body composition and an adverse lipid profile (11,(24)(25)(26)(27). Introduction of GH replacement may induce a favourable change in the very same parameters (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that adult patients with untreated GHD present with a series of cardiovascular risk factors including increased blood pressure, increased BMI, abnormal body composition and an adverse lipid profile (11,(24)(25)(26)(27). Introduction of GH replacement may induce a favourable change in the very same parameters (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Increased mortality ratio is observed in both CD (1) and hypopituitary patients without GH replacement (21)(22)(23)(24)(25), most often related to cardio-and cerebrovascular risk factors. GH replacement has been shown to improve the adverse body composition, cardiovascular risk factors (25,26), and poor QoL associated with GHD (27,28).…”
Section: Analysis Bmentioning
confidence: 99%
“…GH replacement has been shown to improve the adverse body composition, cardiovascular risk factors (25,26), and poor QoL associated with GHD (27,28). In CD, markers of cardiovascular risk remain abnormal for up to 5 years after surgery (29).…”
Section: Analysis Bmentioning
confidence: 99%
“…During the past two decades, evidence has emerged linking hypopituitarism with cardiovascular risk factors, including hyperlipidaemia (11,12,13,14), visceral adiposity (15,16), insulin resistance (17) and vascular endothelial dysfunction (18,19,20).…”
Section: Introductionmentioning
confidence: 99%